2017
DOI: 10.1111/ijfs.13606
|View full text |Cite
|
Sign up to set email alerts
|

Double emulsions (W/O/W): physical characteristics and perceived intensity of salty taste

Abstract: Summary This study addressed the correlation between physical characteristics of double emulsions and sensory perception, as the microstructure of these systems may provide the mechanism to understanding the initial cause of the altered salty taste. Thus, double emulsions (W/O/W) were prepared using different volumes of the internal aqueous phase while maintaining the same fat and sodium contents in the evaluated systems. Polyglycerol polyricinoleate (PGPR) and tween 80 were used as hydrophobic and hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…Two double emulsions (w1/o/w2) with the same fat and sodium content, the emulsion with higher internal water concentration is more salty. Obviously, the structural of double emulsion (w1/o/w2) can reduce the sodium content in food without changing the salty taste 119 . Different physical forms of NaCl have different influences on its dissolution rate and perceived strength, and this can be further studied to explore the best addition method.…”
Section: The Methods Of Reducing Sodiummentioning
confidence: 99%
“…Two double emulsions (w1/o/w2) with the same fat and sodium content, the emulsion with higher internal water concentration is more salty. Obviously, the structural of double emulsion (w1/o/w2) can reduce the sodium content in food without changing the salty taste 119 . Different physical forms of NaCl have different influences on its dissolution rate and perceived strength, and this can be further studied to explore the best addition method.…”
Section: The Methods Of Reducing Sodiummentioning
confidence: 99%
“…The double emulsion was formulated following the procedures from (Paula et al, 2018). The first step was the making of the inner water phase (W1) which was a 1% CaCl2 solution and the outer water phase (W2) which was a 1% guar gum.…”
Section: Double Emulsion Formationmentioning
confidence: 99%
“…203 A recent study addressed the correlation between the physical characteristics of multiple emulsions and the sensory perception of salt. 208 The multiple emulsions were prepared using different volumes of the internal aqueous phase but the same fat and sodium contents. It was found that the saltiness perception could be modulated by changing the structure of the multiple emulsions, which may be useful for developing reduced-sodium foods.…”
Section: ■ Multiple Emulsionsmentioning
confidence: 99%
“…Multiple emulsions have the potential to reduce sodium levels in foods because salt can be encapsulated within the internal aqueous phase and released in burst in the mouth . A recent study addressed the correlation between the physical characteristics of multiple emulsions and the sensory perception of salt . The multiple emulsions were prepared using different volumes of the internal aqueous phase but the same fat and sodium contents.…”
Section: Multiple Emulsionsmentioning
confidence: 99%